Permainan Tradisional dalam Mengembangkan Aktivitas Fisik, Kecerdasan Sosial, dan Emosional: Analisis pada Komunitas Permainan Tradisional - Dwi Budiono; Dian Fitri Anggraini; Ahmad Junaidi (Jurnal Porkes, 2025)
Digital developments have reduced physical activity and social interaction among adolescents, resulting in sedentary lifestyles and challenges in regulating emotions. This study aims to analyze the influence of traditional games on the physical activity, social intelligence, and emotional intelligence of adolescents in cultural communities in Malang City. The method used a mixed-methods design with a one-group pretest-posttest approach on 30 members of the KUAT Community. The structured traditional games intervention was carried out over 8 weeks. Quantitative data were analyzed using the Wilcoxon test, Spearman's correlation, and linear regression; qualitative data were analyzed thematically. The results showed a significant increase in all three variables (p=0.000). Physical activity increased from 45.90 to 87.93; social intelligence from 56.73 to 87.07; and emotional intelligence from 57.73 to 87.90. A strong correlation was found between variables (ρ=0.65–0.78). Physical activity predicted a 54.8% increase in social intelligence and a 42.0% increase in emotional intelligence. Qualitative data revealed learning mechanisms through direct interaction and group dynamics. Conclusion Traditional games in cultural communities are effective as holistic interventions that simultaneously improve the physical, social, and emotional aspects of adolescents.